Determining the Enhancement of Oral Bioavailability VIA Solid Lipid Nanoparticles of Anticancer Drug Dasatinib - An In-vitro Cytotoxicity and Pharmacokinetic Study - Arafath, A. A. Mohamed Yasir; Jaykar, B. (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Objective: Dasatinib (DST) is a Biopharmaceutics Classification System Class II drug having very low solubility and high permeability. Low aqueous solubility and poor dissolution of DST lead to poor bioavailability, Thus, limited aqueous solubility is the bottleneck for the therapeutic outcome of DST. Animal data suggest that the absolute bioavailability of DST is about 14–34% due to an extensive first-pass effect. To overcome hepatic first-pass metabolism and to enhance oral bioavailability, lipid-based drug delivery systems such as solid lipid nanoparticles (SLNs) can be used. Methods: SLNs are submicron colloidal carriers having a size range of 50–1000 nm. These are prepared with physiological lipid and dispersed in water or aqueous surfactant solution. DST can be conveniently loaded into SLNs to improve the oral bioavailability by exploiting the intestinal lymphatic transport. An optimal system was evaluated for bioavailability study in rats compared with that of DST suspension (SUS). Results: An in vitro cytotoxicity study was done by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay method through ATCC cell lines; the percent inhibition was more in SLN when compared with SUS. The pharmacokinetics of DST-SLNs after oral administration in male Wistar rats was studied. The bioavailability of DST was increased by 2.28 fold when compared with that of a DST SUS. Conclusion: The results are indicative of SLNs as suitable lipid-based carrier system for improving the oral bioavailability of DST.